Integrasi Nilai-Nilai Adat Gayo dalam Praktek Ekonomi Syariah: Integration of Gayo Customary Values in Sharia Economic Practice - Wali Ara; Taufiq; Malahayatie (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2025)
The Islamic Economic System integrates moral values with Islamic economic practices to create equitable social welfare, namely integrating the moral values of Gayo tribal customs in Banda Aceh. This research aims to analyze the economic practices of Gayo people in the integration of customs and Islamic economics. The research method uses literature study, namely collecting data and searching literature and documentation such as books, articles and relevant news and analyzing by adjusting relevant data. The results show that the economic practices of the Gayo community, such as the Alang Tulung Beret Berbantu tradition, reflect Islamic economic principles that emphasize justice, togetherness, and solidarity. This gotong royong system is not only a mechanism for distributing labor and production, but also strengthens social and moral values, without relying on conventional markets. Customary values such as order, setie, and semayang/gemasih are in line with Islamic principles such as trust, helping, and keeping contracts. In addition, Gayo economic activity is seen as part of worship, by instilling the values of intention for Allah (niyyah) and working as well as possible (ihsan). This tradition shows that local wisdom can strengthen Islamic business ethics and prevent people from harmful practices. Thus, Gayo's local culture-based economy has the potential to become a model economist.